Influence Training And Motivation Work On The Performance Of Leuwigajah 6 Cimahi State Elementary School Teachers - Melda Eka Suci; Indrajati Wibowo (Sean Institute, 2024)
This study aims to determine the effect of training and work motivation on the performance of teachers of SD Negeri Leuwigajah 6 Cimahi. In this study using quantitative methods with data collection techniques through distributing questionnaires. The sampling technique in this study used saturated sampling technique. The population in this study were 30 teachers of SD Negeri Leuwigajah 6 Cimahi. The analytical tool used in this research is SPSS 22. The results showed that partially (t test) the independent variabels training and work motivation have a significant effect on performance. Simultaneously (f test) shows that thete is a significant influence between the training variables (X1) and work motivation (X2) on performance (Y).